Antimicrobial activity of probiotics against oral pathogens around orthodontic mini-implants: An in vitro study - Lemos, Ivana da Silva; Jassé, Fernanda F. de Albuquerque; Suzuki, Selly Sayuri; Alencar, Cristiane de Melo [UNESP]; Fujii, Denise Nami; Zaniboni, Joissi Ferrari [UNESP]; Suzuki, Hideo [UNESP]; Garcez Segundo, Aguinaldo Silva (FapUNIFESP (SciELO), 2021)
Objective: The aim of this in vitro study was to evaluate the antimicrobial effect of five types of non-industrialized and industrialized probiotics on biofilms formed around orthodontic mini-implants. The null hypothesis tested was: there is no difference in the antimicrobial effect between the five types of probiotics tested around orthodontic mini-implants. Methods: For the experiment, 120 mini-implants were immersed for seven days in Staphylococcus aureus solution for bio-film formation, and were subsequently plated in culture medium containing probiotics. The mini-implants were divided into six different groups, according to the probiotic used: G1) Lacto-bacillus casei; G2) Lactobacillus brevis; G3) Lactobacillus rham-nosus; G4) Lactobacillus from fermented milk Yakult®; G5) Lac-tobacillus from fermented milk Batavito® and G6) without use of probiotic, as negative control. Qualitative and quantitative analyses of all groups were performed using the CFU (colony forming unit) count. Results: The study showed that groups G4 and G6 did not present antimicrobial activity, in comparison to groups G1, G2, G3, and G5 (p < 0.05), which demonstrated antimicrobial activity. Conclusion: The non-commercial probiotic bacteria, Lacto-bacillus casei and Lactobacillus rhamnosus, as well as commercially available fermented milk Batavito® presented promising results in the reduction of colonization of mini-implants by S. aureus. Therefore, the null hypothesis was rejected.
Keywords: Microbiology; Oral hygiene; Probiotics